Architecture of the slovak air traffic management system in relation to the european system - Havel, Karel (Communications - Scientific letters of the University of Zilina, 1999)
This paper outlines an overall CNS/ATM architecture, its components flow between (common functional architecture) and functional blocks allocation to the organisational units (system architecture). It does not represent the final architecture but defines the technical framework for the harmonisation and integration efforts. It is the baseline for the specification work for implementation in 2001-2005 in the framework of the EATCHIP Work Programme, serves as an information source for local planning actions by the national administration, serves, at a lower level of decomposition, as a framework for detailed architecture work, and is a baseline for the SATMS development.